Characterisation of impaired wound healing in a preclinical model of induced diabetes using wide‐field imaging and conventional immunohistochemistry assays. Issue 1 (1st October 2018) - Saidian, Mayer; Lakey, Jonathan R.T.; Ponticorvo, Adrien; Rowland, Rebecca; Baldado, Melissa; Williams, Joshua; Pronda, Maaikee; Alexander, Michael; Flores, Antonio; Shiri, Li; Zhang, Stellar; Choi, Bernard; et al.
Abstract : Major complications of diabetes lead to inflammation and oxidative stress, delayed wound healing, and persistent ulcers. The high morbidity, mortality rate, and associated costs of management suggest a need for non‐invasive methods that will enable the early detection of at‐risk tissue. We have compared the wound‐healing process that occurs in streptozotocin (STZ)‐treated diabetic rats with non‐diabetic controls using contrast changes in colour photography (ie, Weber Contrast) and the non‐invasive optical method Spatial Frequency Domain Imaging (SFDI). This technology can be used to quantify the structural and metabolic properties of in‐vivo tissue by measuring oxyhaemoglobin concentration (HbO2 ), deoxyhaemoglobin concentration (Hb), and oxygen saturation (StO2 ) within the visible boundaries of each wound. We also evaluated the changes in inducible nitric oxide synthase (iNOS) in the dermis using immunohistochemistry. Contrast changes in colour photographs showed that diabetic rats healed at a slower rate in comparison with non‐diabetic control, with the most significant change occurring at 7 days after the punch biopsy. We observed lower HbO2, StO2, and elevated Hb concentrations in the diabetic wounds. The iNOS level was higher in the dermis of the diabetic rats compared with the non‐diabetic rats. Our results showed that, in diabetes, there is higher level of iNOS that can lead to an observed reduction in HbO2 levels. iNOS is linked to increased inflammation, leading to prolonged wound healing. Our results suggest that SFDI has potential as a non‐invasive assessment of markers of wound‐healing impairment.